Ethyl 2-(4-hydroxy-1-methyl-2-oxo-1,2-dihydroquinolin-3-yl)acetate - Ukrainets, Igor V. (International Union of Crystallography, 2009)
In the title compound, C(14)H(15)NO(4), the bicyclic fragment and the ester group form a dihedral angle of 86.7 (2)°. Intermolecular O—H⋯O and C—H⋯O hydrogen bonding connects molecules into a helix along the crystallographic b axis.